Tinjauan Al-Qur’an dan Hadits Tentang Manajemen Waktu (Literature Review) - Aprima, Septi Gia; Arnol, Arnol; Satriadi, Inong (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find out the concept of time management in the perspective of the Qur'an and Hadith. This research was carried out using a qualitative approach using the literature review method. Various sources were analyzed, namely the Qur'an and Hadith as the main sources of research data, as well as research results published through various journals on the google scholar website. Data generation is carried out using the keywords